The Buprestidae (Coleoptera, Buprestoidea) of the Tuscan Archipelago (Italy) - Leonardo Forbicioni; Nicola Tormen; Gianfranco Curletti; Luciano Bani; Andrea Di Giulio; Enrico Ruzzier (Biodiversity Data Journal, 2024)
Buprestidae is a group of beetles of important conservation and phytosanitary value that is poorly studied in the Tuscan Archipelago and the limited faunistic knowledge available refers to a few scant historical records.The present contribution increments the species documented in the Archipelago from 27 to 51, providing more than 300 georeferenced occurrence records, derived from both direct field research and citizen science via iNaturalist. Of particular importance is the discovery of Eurythyrea quercus on Isola d'Elba, an uncommon and localised species currently critically endangered.